Effects of Industry 4.0 on Small and Medium-Scale Enterprises: An Analytical and Bibliometric Review - Kafilah Lola Gold (SAGE Open)
Small and medium-scale enterprises (SMEs), the backbone of the global economy, face a significant risk of falling behind in the digital age of adapting to Industry 4.0 (4IR) technologies. This study presents an analytical and bibliometric review of the effects of 4IR on SMEs worldwide, based on empirical research published from 2013 to 2023. Using the analytical methodology and the Web of Science database (WoS), the review identifies and analyses 30 relevant empirical studies conducted across various regions and industries, employing VoSviewer for bibliometric analysis to shed light on the challenges and opportunities that 4IR adoption presents for SMEs. Key themes emerge, including the role of digitalisation in boosting SMEs’ productivity, competitiveness and sustainability. However, the findings reveal that while European, Asian, and American SMEs lead in technology adoption, a concerning disparity exists between developed and developing countries regarding 4IR adoption rates, with the latter facing challenges such as limited resources, inadequate infrastructure, and insufficient technical expertise. To bridge this gap, the study suggests implementing targeted support programmes, including financial incentives, skill development initiatives, and enhanced access to technologies to help SMEs in developing regions leverage 4IR technologies. The review encourages policymakers to prioritise these strategies to promote inclusive economic growth and emphasises the importance of future research in addressing knowledge gaps. Future research should focus on quantitative studies exploring the economic impact of 4IR adoption on SMEs and identifying region-specific strategies to mitigate adoption barriers, particularly in underrepresented regions such as Africa and the Middle East. By understanding the complex dynamics of SMEs’ engagement with 4IR, this research provides actionable insights for policymakers, practitioners and researchers seeking to navigate a successful digital transformation journey. Jel Classification: O3, L26.